Bio-efficacy of various readymix synthetic insecticides against pest complex of ’H 6’ cotton (Gossypium hirsutum) - PATEL, B H; PATEL, D M; PATEL, M J; PATEL, J R (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995-96 and 1996-97 to study the bio-efficacy of readymix synthetic insecticides against pest complex of’H 6’ cotton (Gossypium hirsutum L.) and their effect on yield. The result revealed that a mixture of deltamethrin with triazophs (12.5 + 437.5 g ai/ha) Could manage the bollworm Population, whereas endoaulfan + triazophos (500 + 500 g ai/ha) gave effective control of the sucking pest complex. Spray of deltamethrin + triazQphos (10+ 350 g ai) and endosulfan + triazophos (625 + 625 g ai/ha) gave higher protection to the buds, bolls and loculi against bollworms which reflected on higher seed cotton yield. The highest cost benefit ratio (ICBR 1:12:29) was obtained from the ’H 6’ cotton protected with deltamethrin + triazophos (10 + 350 g ai/ha).